Pro Java clustering and scalability : building real-time apps with Spring, Cassandra, Redis, Websocket and RabbitMQ - Acetozi, Jorge (Apress, 2017)
Build clustered and scalable Java-based, real-time applications using Spring Framework, Boot, WebSocket, Cassandra, Redis and RabbitMQ. In this book, you'll tie all this together with a dive-in case study, a real-time scalable chat application under differing scenarios. Pro Java Clustering and Scalability also discusses how to horizontally scale the WebSocket chat application using a full STOMP broker such as RabbitMQ. Although this is a programming book, it also discusses many interesting infrastructure topics and tips about continuous delivery, Docker, NoSQL (Cassandra and Redis) and other related technologies. You will: Handle clustering and scalability using various open source Java, microservices, and web services tools and technologies Use Spring Framework, Boot, and other Spring technologies Integrate with Redis, RabbitMQ, Cassandra, NoSQL, and much more; test the case study code under various scenarios and stresses.